Loyalitas Pelanggan : Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan Pada Rumah Sakit Umum Syaiful Anwar Malang - Prasetyo Isbandono, (Bisnis dan Manajemen, 2009)
Hospital is one of government institution have responsibility to serve public healt. To reach that purpose, this institution must be increase services betterto creted costumer satisfaction. Hypotesis on this research ; 1) To know direct real influence Services Quality (Tanggible, Reliabiity, Responsiveness, Assurance and Emphaty) and Costumer Satisfaction to costumer Loyality, 2) To know Costumer Satisfaction as intervening variable between Services Quality and Costumer Loyality. Location on this research is Rumah Sakit Syaiful Anwar Malang. This research used explanatory research with survey approach.. Analisys Methode used Structural Equation Model (SEM) with Analysis of Moment Structure (AMOS) 4.0 version. The finding reported here reveal that there are 1) Services Quality have positive infuences with Costumer Loyality, 2) Services Quality have positive infuences with Costumer Satisfaction, 3) Costume Satisfaction are positive intervening variable between Sevices Quality and Costumer Loyality.